Renal cyst masses (Bosniak category II–III) may be over evaluated by the Bosniak criteria based on MR findings. Issue 51 (December 2017) - Zhong, Jianguo; Cao, Fang; Guan, Xiaojun; Chen, Junfa; Ding, Zhongxiang; Zhang, Minming
Abstract : Abstract: A classification system of renal cysts developed by Bosniak is based on computed tomography (CT) findings and has been applied to deal with the complex cystic renal masses. Magnetic resonance (MR) has excellent soft-tissue resolution, it has been used to further evaluate some complex renal lesions, especially those suspected of containing soft tissue components and hyperattenuating cystic lesions seen on CT. Compared with CT, MR images may find additional information, which may lead to inconsistent classification. However, at present, there is no consensus on the treatment of these inconsistent lesions. This study aimed to investigate the value of MR in the evaluation of renal cystic masses by using the Bosniak classification system and improve understanding of the MR features of renal cyst masses. The present study retrospectively analyzed 35 renal cyst masses in 34 patients (10 men and 24 women with age from 20 to 65 years old, with an average of 49 ± 12.08), who underwent both MR and computed tomography (CT) examinations within 6 months (range from 1 to 135 days with an average of 11 ± 24.16 days). Twenty-four lesions (9 category III and 15 category IV on CT) received surgical treatment, 4 category IIF lesions on CT were upgraded to category III on MR, which were finally accepted operative resection. The remaining 7 lesions (category II–IIF on both CT and MR) were followed up for at least 3 years. For each lesion, size of both cyst and solid component, presence of calcification, number of septa, thickness of wall and septa, and appearance of enhancement were analyzed. Each lesion was categorized by using Bosniak criteria on CT and MR, respectively. The MR findings were compared with CT and pathology or follow-up results. On MR, categories of the lesions were as follows: category IIF (n = 7), III (n = 12), IV (n = 16). On CT, categories of the lesions were as follows: II (n = 3), IIF (n = 8), III (n = 9), and IV (n = 15). Findings on MR and CT images were inconsistent in 8 (23%) lesions. Among them, 3 category II lesions on CT were classified as category IIF on MR images, 4 category IIF lesions on CT were upgraded to category III on MR, and 1 category III lesions to category IV. In these lesions, MR detected more increased wall/septa thickness (n = 8) and septa number (n = 3) than CT, resulting in an upgrade in classification. Based on the pathological results, 5 of category III (5/9, 56%) and all category IV (15/15, 100%) lesions on CT images were malignant. On MR, 4 of category III (4/12, 33%) and all category IV (16/16, 100%) lesions were malignant. The renal cyst masses in some cases, especially category II to III lesions, may be over evaluated by the Bosniak criteria based on MR findings. It is necessary to combine MR features with CT findings in evaluation and management of these cases with renal cystic masses.